1991
DOI: 10.1093/ajcn/54.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of subcutaneous adipose tissue and diet in postmenopausal US women

Abstract: The distributions of fatty acids in subcutaneous-adipose-tissue aspirates and their relation to intake as assessed by a semiquantitative food-frequency questionnaire were investigated in 115 postmenopausal US women free from cancer. Percentages of fatty acids in adipose tissue were significantly correlated with the percentage of total fat intake for polyunsaturated fatty acids (Spearman correlation = 0.37), n-3 fatty acids of marine origin (Spearman correlation = 0.48), and trans fatty acids (Spearman correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
3
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(117 citation statements)
references
References 27 publications
3
110
3
1
Order By: Relevance
“…34,35 Published correlation coefficients between TFA intake (as percentage of total fat) estimated from FFQ and the proportion of TFA in adipose tissue have varied between 0.29 and 0.67. [36][37][38][39][40] Biomarkers may provide a more accurate measure of TFA intake than obtained with FFQ since biomarkers of dietary intake are not affected by the participants' memory or differential reporting. However, it is not possible to quantify TFA intakes from proportions of TFA in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Published correlation coefficients between TFA intake (as percentage of total fat) estimated from FFQ and the proportion of TFA in adipose tissue have varied between 0.29 and 0.67. [36][37][38][39][40] Biomarkers may provide a more accurate measure of TFA intake than obtained with FFQ since biomarkers of dietary intake are not affected by the participants' memory or differential reporting. However, it is not possible to quantify TFA intakes from proportions of TFA in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The FFQ, which has been extensively validated in adults (Willett et al, 1987;London et al, 1991;Stryker et al, 1991;Hu et al, 1999), consists of a list of 147 food items that represent the major sources of multiple nutrients. The FFQ also contains a section where a subject can indicate foods, not otherwise listed in the survey, that are consumed at least once a week.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the mammary glands, shorter chain fatty acids are synthesized due to the presence of a tissue-specific chainterminating enzyme, thioesterase II ( Thompson and Smith, 1985). All three fatty acids (14:0, 15:0 and 17:0) are also present in ruminant fat (beef and lamb meat) and in fat from fish, but generally, dairy products are the main source.The fatty acid composition of adipose tissue partly reflects the relative proportion of fatty acids in the diet (London et al, 1991), and Wolk et al (1998 have shown that the content of 14:0, 15:0 and 17:0 in adipose tissue and serum lipid fractions are valid biomarkers for long-term intake of dairy fat in populations with high intake of such products. In epidemiologic studies, use of biomarkers may provide a more accurate and objective measure for long-term intake than information from dietary questionnaires.…”
mentioning
confidence: 99%